High-throughput class I HLA genotyping using fluorescence resonance energy transfer (FRET) probes and sequence-specific primer-polymerase chain reaction (SSP-PCR). - Gelsthorpe, A; Wells, R; Lowe, A; Tonks, S; Bodmer, J; Bodmer, W (1999)
We have developed a semi-automated HLA class I typing system utilising TET/TAMRA-labelled fluorescence resonance energy transfer (FRET) hydrolysis probes. The results from 87 individuals are in full concordance with serology and conventional gel-based systems. This assay replaces labour-intensive conventional gel-based DNA typing and has a higher allelic resolution than serology. Our approach differs from previously published fluorogenic probe typing protocols in that it provides simultaneous typing of HLA-A, -B and -C loci to medium resolution. Furthermore, by using equipment that is not specific to FRET probe analysis our system has in-built expansion capacity to 384 reactions per plate, thus making it applicable to high-throughput population screening. Automation is achieved through the use of computer software which analyses direct input from the fluorescence reader, allowing high throughput with a low inherent error rate.